MBNGUKUR KELAYAKAN INVESTASI ANTARA MEMBELI DAN MENYBWA MESIN PRODUKSI STUDI KASUS PT PORTER REKAYASA UNGGUL - , Theresia Radita Rosari; , Dr. Erni Ekawati, M.B.A, M.S.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this research is to determine investment condition of PT. Porter Rekayasa Unggul between leasing or buying machine. Research method used is descriptive analysis with case study approach. Analysis tools in the test method used was Capital Budgeting with NPV (Net Present Value), IRR (Internal Rate of Return), Sensitivity Analysis and Scenario Analysis method to determine the best investment decision between leasing or buying machine. The result of the research says that leasing is more valuable than buying machine. Leasing method is more effective and efficient for operational of the Company.